Modal identification of bridges based on continuous dynamic monitoring - Xu, Min (2017)
The identification of modal parameters of bridges based on ambient vibration measurements has motivated an increased interest as a tool for detection and diagnosis of small changes in vibratory characteristics and, thus, provides important information to support an efficient maintenance policy. However, the large volume of data continuously produced by a dynamic monitoring system requires an automatic data processing to extract the modal parameters. This paper presents an integrated system developed for this purpose and its application to the data collected from a large cable-stayed bridge.